Prognostic Value of B‐Type Natriuretic Peptide in Liver Transplant Patients: Implication in Posttransplant Mortality. Issue 1 (15th June 2021) - Kwon, Hye‐Mee; Moon, Young‐Jin; Kim, Kyoung‐Sun; Shin, Won‐Jung; Huh, In‐Young; Jun, In‐Gu; Song, Jun‐Gol; Hwang, Gyu‐Sam
Abstract : Background and Aims: Despite frequent cirrhotic cardiomyopathy or subclinical heart failure (HF), the prognostic value of peri–liver transplant (LT) B‐type natriuretic peptide (BNP) has been poorly studied in advanced liver disease. We examined the association between BNP and mortality in a large cohort of LT patients and identified risk factors for peri‐LT BNP increase. Approach and Results: Using prospectively collected data from the Asan LT Registry between 2008 and 2019, 3, 811 patients who measured serial pretransplant BNP (preBNP) and peak BNP levels within the first 3 posttransplant days (postBNPPOD3 ) were analyzed. Thirty‐day all‐cause mortality predicted by adding preBNP and/or postBNPPOD3 to the traditional Revised Cardiac Risk Index (RCRI) was evaluated. PreBNP > 400 pg/mL (known cutoff of acute HF) was found in 298 (7.8%); however, postBNPPOD3  > 400 pg/mL was identified in 961 (25.2%) patients, specifically in 40.4% (531/1, 315) of those with a Model for End‐Liver Disease score (MELDs) > 20. Strong predictors of postBNPPOD3  > 400 pg/mL were preBNP, hyponatremia, and MELDs, whereas those of preBNP > 400 pg/mL were MELDs, kidney failure, and respiratory failure. Among 100 (2.6%) post‐LT patients who died within 30 days, patients with postBNPPOD3  ≤ 150 pg/mL (43.1%, reference group), 150‐400 pg/mL (31.7%), 400‐1, 000 pg/mL (18.5%), 1, 000‐2, 000 pg/mL (4.7%), and >2, 000 pg/mL (2.0%) had 30‐day mortalities of 0.9%, 2.2%, 4.0%, 7.7%, and 22.4%, respectively. Adding preBNP, postBNPPOD3, and both BNP to RCRI improved net reclassification index to 22.5%, 29.5%, and 33.1% of 30‐day mortality, respectively. Conclusions: PostBNPPOD3  > 400 pg/mL after LT was markedly prevalent in advanced liver disease and mainly linked to elevated preBNP. Routine monitoring of peri‐LT BNP provides incremental prognostic information; therefore, it could help risk stratification for mortality as a practical and useful biomarker in LT.